2018
DOI: 10.1016/j.jocm.2018.09.001
|View full text |Cite
|
Sign up to set email alerts
|

When do social cues and scientific information affect stated preferences? Insights from an experiment on air pollution

Abstract: Stated preference surveys are usually carried out in one session, without any follow-up interview after respondents have had the opportunity to experience the public goods or policies they were asked to value. Consequently, a stated preference survey needs to be designed so as to provide respondents with all the relevant information, and to help them process this information so they can perform the valuation exercise properly. In this paper, we study experimentally an elicitation procedure in which respondents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…In their robust literature review, Albarracin and Shavitt (2018) conclude that well-established individual attitudes about any specific topic tend to be quite persistent and that any single message or informational intervention has limited influence on changing attitudes. Specific to the effects of information in stated preference work, Ami et al (2018) find that a majority of respondents never change their willingness to pay values despite receiving various kinds of information throughout an experiment related to air pollution. Only about a quarter of respondents revised their willingness to pay values after receiving scientific information.…”
Section: Literature Reviewmentioning
confidence: 96%
See 1 more Smart Citation
“…In their robust literature review, Albarracin and Shavitt (2018) conclude that well-established individual attitudes about any specific topic tend to be quite persistent and that any single message or informational intervention has limited influence on changing attitudes. Specific to the effects of information in stated preference work, Ami et al (2018) find that a majority of respondents never change their willingness to pay values despite receiving various kinds of information throughout an experiment related to air pollution. Only about a quarter of respondents revised their willingness to pay values after receiving scientific information.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Specific to the effects of information in stated preference work, Ami et al. (2018) find that a majority of respondents never change their willingness to pay values despite receiving various kinds of information throughout an experiment related to air pollution. Only about a quarter of respondents revised their willingness to pay values after receiving scientific information.…”
Section: Introductionmentioning
confidence: 99%
“…However, many findings show that respondents involved in preference elicitation surveys are often not familiar and often do not hold appropriate information on the ecosystem goods and services being assessed (Whitehead and Blomquist, 1991;Hanley and Munro, 1992;Spash and Hanley, 1995;Blomquist and Whitehead, 1998;Lewan and Söderqvist, 2002;LaRiviere et al, 2014;Brahic and Rambonilaza, 2015;Czajkowski et al, 2016;Ami et al, 2018;De Ville D'Avray, 2018). Realistically, some ESs are clearly perceived by people while others are not (De Groot et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the supply of academic information only targets to increase the cognitive knowledge of the recipient citizens. For instance, Ami et al (2018) reported that the impact of scientific information about the effects of air pollution on respondents' preferences, expressed as their willingness to pay (WTP) values, was strong. A proportion of people (30%) receiving scientific information revised their WTP upwards relative to the mean WTP value.…”
Section: Introductionmentioning
confidence: 99%
“…AHP is based on a decision maker’s judgment matrix, which summarizes the pairwise comparison results of the relative priorities of criteria (Saaty 2008 ). However, since only two criteria are compared each time, it is not easy to make all pairwise comparison results fully consistent (Benítez et al 2011 ; Ami et al 2018 ). To overcome this difficulty, an intuitive approach is to ask the decision maker to modify his/her pairwise comparison results (Lin and Yang 1996 ).…”
Section: Introductionmentioning
confidence: 99%